Realisation of acoustic black holes using multi-material additive manufacturing - Austin, Beth; Cheer, Jordan (Frontiers in Physics, 2022)
Acoustic black holes (ABHs) have been widely accepted as an effective passive vibration control technique, with multiple configurations investigated for different applications. However, traditional manufacturing techniques may limit the potential geometries and configurations of the ABH. For example, the required damping layer has to be applied to the surface of the ABH taper rather than being embedded throughout or within the taper. In addition, conventional subtractive manufacturing is particularly wasteful for the realisation of ABHs, which rely on the removal of material to create a tapering structure. Therefore, in this work, we investigate the use of multi-material additive manufacturing as a potential solution, which avoids waste material in the manufacturing process and is capable of realising complex geometries, such as enclosing one material inside another. An ABH taper in a beam termination application has been implemented using polymer multi-material inkjet printing. The additively manufactured ABH was modelled using finite element analysis, before being manufactured and experimentally tested to enable an investigation of the vibration attenuation capabilities of such an ABH realisation.